INVESTASI SEKURITAS DERIVATIF DI PASAR MODAL INDONESIA - Sayyid, Annisa (IAIN Antasari, 2014)
The world will never forget about the big shock in capital market in America âBlack October eventâ or Black Tuesday that occurred in 1929 and known as The Great Depression that cause fall in world economy. However, there is always have a wisdom behind an event, that is the birth of a new investment product called derivative instrument. The derivative instrument is a financial instrument that constitute derivative asset from the underlying asset, both derived from stocks and bonds. There are There are several kinds of derivative securities which warrant, right, option, forward, futures, and swap. In Indonesia, although it is still new, investment od derivative instrumen looks like the âfresh windâ for investor amid tight and hard competition finance business. The proof, many big companies are investing in derivative securities such as, Quaker Oats were issued Future, Indosat Warrant issued, as well as issuing the Right of Niaga Bank.Â